SPECTROPHOTOMETRY ANALYSIS OF DEEP-SEA SEDIMENTS ALONG THE MAIN PATHYWAY OF THE INDONESIAN THROUGHFLOW: SPATIAL VIEW - Nurhati, Intan Suci (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2016)
Deep-sea sediment is the primary marine archive for reconstructing climate of the past millennia. With an array of geochemical analyses and more techniques to be developed, conservative sample usage is necessary. This study presents spectrophotometry analysis as a non-intrusive approach on deep-sea sediment samples retrieved along the main pathway of the Indonesian Throughflow in the Makassar Strait. Sediments from 25 sites including: Eastern Kalimantan, western Sulawesi, south Makassar Strait, southern Sulawesi and northern Bali are scanned as wet and dried samples over the visible spectra (400-700nm). After taking first derivatives of the raw data to accentuate the signals, R-mode factor analysis is applied to reveal three factors that explain 96.99% variance. Factor 1, which explains 53.94% variance, is characterized as halite. Factor 2 (30.89%) is carbonate and Factor 3 (12.18%) is kaolinite or clay mineral. XRD analysis reveals the presence of calcite, quartz, halite, plagioclase and aragonite, with the first three being the most prevalent minerals. Spatial distribution map of Factor 1 (halite) shows higher values in eastern Kalimantan, south Makassar Strait and western Sulawesi. Factor 2 (carbonate) is relatively high in eastern Kalimantan, southern Sulawesi and northern Bali; with similar observation at the first two sites from accompanying carbonate content analysis. Relatively high Factor 3 (kaolinite) in eastern Kalimantan is consistent with its proximity to the Mahakam River delta. Characteristics of each region are further discussed herein. Taken together, this information lays a foundation for applying the non-intrusive spectrophotometry downcore to study past climate change in the Makassar Strait.